Kinerja Lingkungan, Kepemilikan Manajerial dan Nilai Perusahaan - Suniantari, I Gusti Ayu Putri; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi; Vol 32 No 2 (2022), 2022)
Investors have a perception of the level of success of the company reflected in the stock price which is called firm value. The fluctuation of stock price movement is the phenomenon related to the firm value. This research aims to determaine the effect of environmental performance and managerial ownership on firm value. Sampling of mining sector listed on the IDX in 2016–2019 in this study using a purposive sampling technique which resulted in 36 observations. Multiple linear regression is used as a data analysis technique in this study. This research obtained the results of environmental performance and managerial ownership have a positive effect on firm value. The research implications theoretically support agency theory and legitimacy theory. The practical implication of this research can be used as consideration in decision making by investors and company management. Keywords: Environmental Performance; Managerial Ownership; Firm Value.